On ‘Systematic theology’ and the contested shape of a discipline - Westerholm, Martin (Stellenbosch Theological Journal, 2023)
This essay takes up questions about how systematic theology can understand itself in light of critical questions about the functioning of the label. In face of concerns about the exclusionary functioning of the term, the essay develops a set of philosophical distinctions that may help theologians to understand the shape of their discipline. The picture that emerges is of a discipline that is constituted by shifting constellations of historical precedents rather than rigid boundaries; that moves through epistemic justice for the sake of discovering truth, which furthers the pursuit of wider forms of justice; and that functions hermeneutically rather than analytically or critically in its understanding of language.